Planning, Implementation and Reflection on the Teaching of the Ringkang Jawari Dance at a Senior High School in Serang Regency - Wiwin Purwinarti; Asep Muhyidin; Aan Hendrayana (Research in Education, Technology, and Multiculture, 2026)
Culture-based arts education is gaining increasing attention in the development of contextual education focused on cultural preservation. However, research on teachers' experiences in teaching traditional dance, particularly the Ringkang Jawari dance, remains relatively limited. This study aims to explore the experiences of arts and culture teachers in planning, implementing, and reflecting on Ringkang Jawari dance lessons in secondary schools. The study employed a qualitative, phenomenological approach to understand teachers' subjective experiences in the learning process. Data were collected through in-depth interviews, participant observation, and documentation of cultural arts teachers involved in traditional dance instruction. Data analysis was conducted thematically through the processes of reduction, categorization, and interpretation of participants' experiences. The research findings revealed four main themes. Firstly, lesson planning was understood as a process of adapting the school curriculum to the local cultural values embodied in the Ringkang Jawari dance. Secondly, the implementation of the learning process demonstrated experience-based pedagogical practices that emphasized students' active engagement through the exploration of movement, collective work, and cultural interpretation. Thirdly, teachers' reflections were an important part of learning evaluation and a means of continuous professional development. Fourthly, emotional and social dimensions emerge as integral elements that foster interpersonal relationships, self-confidence, and cultural appreciation among students. The research findings indicate that traditional dance learning is not merely focused on technical skills but is also a cultural, reflective, and social process. This research contributes to the development of the Experiential Reflective Cultural Pedagogy Model (ERCP) as a contextual, participatory, and reflective model of arts and culture education and provides implications for strengthening culture-based arts education in schools.Keywords: Teacher experience, Arts and culture education, Ringkang Jawari dance, Reflective learning, Arts education, phenomenology.